2012
DOI: 10.1063/1.4751247
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and amplitude stabilized terahertz quantum cascade laser as local oscillator

Abstract: We demonstrate an experimental scheme to simultaneously stabilize the frequency and amplitude of a 3.5 THz third-order distributed feedback quantum cascade laser as a local oscillator. The frequency stabilization has been realized using a methanol absorption line, a power detector, and a proportional-integral-derivative (PID) loop. The amplitude stabilization of the incident power has been achieved using a swing-arm voice coil actuator as a fast optical attenuator, using the direct detection output of a superc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…The ability to operate terahertz frequency quantum cascade lasers 1 (THz QCLs) in continuous-wave (CW) is essential for many applications, including their use in local oscillator systems, 2 spectroscopy/trace-gas detection, [3][4][5][6] and direct bolometric imaging. 7 It is also often important to ensure that the lasers have low dissipated power.…”
mentioning
confidence: 99%
“…The ability to operate terahertz frequency quantum cascade lasers 1 (THz QCLs) in continuous-wave (CW) is essential for many applications, including their use in local oscillator systems, 2 spectroscopy/trace-gas detection, [3][4][5][6] and direct bolometric imaging. 7 It is also often important to ensure that the lasers have low dissipated power.…”
mentioning
confidence: 99%
“…We have not measured the absolute power of this particular laser since we are more interested in the ratio. However, based on the power measurement of a similar laser [5], we expect the maximal output power of the forward direction to be about 0.8 mW, while the other direction is 0.45 mW. Prior to frequency locking, we measure methanol absorption lines by sweeping the QCL bias voltage from 13.5 to 14.5 V, which tunes the frequency electrically, as confirmed by a separate FTS measurement.…”
Section: Resultsmentioning
confidence: 99%
“…In general, since the QCL is not inherently frequency stable, a system of frequency or phase locking [3,4] is required. So far, the radiation emitted from only one direction of the QCL has been used for both pumping a mixer and stabilizing the frequency of the source [5]. In this way, to achieve frequency locking, part of the beam power is unavailable for the mixer.…”
Section: Introductionmentioning
confidence: 99%
“…topological insulator properties) [89]. It is worth mentioning the importance of this new class of device for amplitude and frequency stabilization of QCLs in metrological grade spectroscopy [90][91][92][93]. Naming all the possible applications of THz active devices in gas-and solid-state spectroscopy, from sensing to healthcare to investigation of novel state of matter and materials, could be per se the topic of another review, as the one reported recently in Ref.…”
Section: Applicationsmentioning
confidence: 99%